Using context in information literacy instruction : beyond basic skills - Hosier, Allison (Chicago: ALA editions, 2022)
"Hosier shows academic librarians how to use context when teaching information literacy, an approach that offers a substantive and enduring impact on students' lifelong learning"--
Introduction: The Next Step for Information Literacy -- Understanding the Contextual Nature of Research -- Teaching the Contextual Nature of Research -- How Research Starts and the Importance of Context -- Appropriate Sources (and How to Find Them): Considering Context -- Evaluating Information Through a Contextual Lens -- The Role of Context in Using Information -- Creating Information with Context in Mind -- Appendix A. Annotated Bibliography Project -- Appendix B. Example Assessment Questions.
Includes bibliographical references and index.
Keywords: Information literacy -- Study and teaching (Higher); Research -- Methodology -- Study and teaching (Higher); Research -- Classification